Enterprising women in Southern Africa: When does land ownership matter? - Zuzana Brixiová; Thierry Kangoye; Fiona Tregenna (Global Labor Organization (GLO), 2020)
Limited access to finance is one of the major barriers for women entrepreneurs in Africa. This paper presents a model of start-ups in which firms' sales and profits depend on their productivity and access to credit. However, due to the lack of collateral assets such as land, female entrepreneurs have more constrained access to credit than do men. Testing the model on data from the World Bank Enterprise Surveys in Eswatini, Lesotho, and Zimbabwe, we find land ownership to be important for female entrepreneurial performance in terms of sales levels. This finding suggests that the small Southern African economies would benefit from removing obstacles to women's land tenure and enabling financial institutions to lend against movable collateral. While land ownership is linked with higher sales levels, it seems less critical for sales growth and innovation where access to short term loans for working capital seems to be key.
Keywords: G21; L26; D24; O17; 330; entrepreneurial sales; innovation; credit; land; gender; Africa